혈관내피세포에서 Vibrio vulnificus Cytolysin이 Caspase-3 활성화를 통한 아프토시스 유발 - 박병현; Byung Hyun Park; 권강범; Kang Beom Kwon; 이영훈; Young Hoon Lee; 장재한; Jae Han Jang; 박진우; Jin Woo Park (Journal of bacteriology and virology, 2001)
Previous studies showed that exposure to Vibrio vulnificus cytolysin (VVC) caused characteristic morphologic changes and dysfunction of vascular structures in lung. VVC showed cytotoxicity to cultured mammalian cells and acted as a vascular permeability factor. In this study, the underlying mechanism of VVC-induced cytotoxicity was investigated by causing ECV304 cell, a human vascular endothelial cell line. Apoptosis, as demonstrated by oligonucleosomal DNA fragmentation and light microscopy, was induced 24 h after VVC treatment, which was prevented by a caspase-3 inhibitor, Ac-DEVD-CHO. Activation of caspase-3 was maximal at 6 h and led to the cleavage of 116 kDa poly (ADP-ribose) polymerase (PARP) with accumulation of the 85 kDa cleavage products. Both activation of caspase-3 and cleavage of PARP were blocked by pretreatment with either antioxidants or caspase-3 inhibitor, but not with caspase-1 inhibitor. VVC increased the production of intracellular peroxide, which could be blocked by catalase. These results indicate that VVC-induced apoptosis is triggered by the generation of hydrogen peroxide, the activation of caspase-3, the degradation of PARP, and the DNA fragmentation. The induction of apoptosis in endothelial cells by VVC may provide a pivotal mechanism for understanding the pathophysiology of VVC-induced septicemia.